Extending Injury- and Disease-Resistant CNS Phenotypes by Repetitive Epigenetic Conditioning - Gidday, Jeffrey M. (Frontiers in Neurology, 2015)
Significant reductions in the extent of acute injury in the CNS can be achieved by exposure to different preconditioning stimuli, but the duration of the induced protective phenotype is typically short-lasting, and thus is deemed as limiting its clinical applicability. Extending the period over which such adaptive epigenetic changes persist – in effect, expanding conditioning’s “therapeutic window” – would significantly broaden the potential applications of such a treatment approach in patients. The frequency of the conditioning stimulus may hold the key. While transient (1–3 days) protection against CNS ischemic injury is well established preclinically following a single preconditioning stimulus, repetitively presenting preconditioning stimuli extends the duration of ischemic tolerance by many weeks. Moreover, repetitive intermittent postconditioning enhances post-ischemic recovery metrics and improves long-term survival. Intermittent conditioning is also efficacious for preventing or delaying injury in preclinical models of chronic neurodegenerative disease, and for promoting long-lasting functional improvements in a number of other pathologies as well. Although the detailed mechanisms underlying these protracted kinds of neuroplasticity remain largely unstudied, accumulating empirical evidence supports the contention that all of these adaptive phenotypes are epigenetically mediated. Going forward, additional preclinical demonstrations of the ability to induce sustained beneficial phenotypes that reduce the burden of acute and chronic neurodegeneration, and experimental interrogations of the regulatory constructs responsible for these epigenetic responses, will accelerate the identification of not only efficacious but also practical, adaptive epigenetics-based treatments for individuals with neurological disease.